Effect of refining on the fatty acid, sterol and tocopherols compositions of soybean oil from GM seeds - Amaral, Joana S. (2008)
Soybeans are an exceptional source of polyunsaturated fats, high quality proteins and high levels of vitamin E, being part of the human diet mainly as vegetable oil and as source of protein. Nowadays, soybean oil represents almost 30% of the world’s vegetable oil production. As most vegetable oils, crude soybean oil must be refined in order to remove unacceptable materials, such as phospholipids, free fatty acids and pigments, that cause a decrease in the product quality. Nevertheless, during this process, desirable components such as phytosterols, tocopherols and polyphenols can be lost. The aim of this work was to study the compositional evolution during extraction and refining processes of soybean oil.